Facing Social Class : How Societal Rank Influences Interaction - Markus, Hazel Rose; Fiske, Susan T. (Book collections on Project MUSE., 2012)
Introduction: a wide-angle lens on the psychology of social class / Hazel Rose Markus and Susan T. Fiske -- Pervasive ideas and social class -- Sociological perspectives on the face-to-face enactment of class distinction / Paul DiMaggio -- The class culture gap / Joan C. Williams -- Institutions and social class -- Class, cultural capital, and institutions : the case of families and schools / Annette Lareau and Jessica McCrory Calarco -- It's your choice : how the middle-class model of independence disadvantages working-class Americans / Nicole M. Stephens, Stephanie A. Fryberg, and Hazel Rose Markus -- Interactions and social class -- Dejà vu : the continuing misrecognition of low-income children's verbal abilities / Peggy J. Miller and Douglas E. Sperry -- Class rules, status dynamics, and "gateway" interactions / Cecilia L. Ridgeway and Susan R. Fisk -- The intersection of resources and rank : signaling social class in face-to-face encounters / Michael W. Kraus, Michelle L. Rheinschmidt, and Paul K. Piff -- Individuals and social class -- Behavioral decision research, social class, and implications for public policy / Crystal C. Hall -- When hard and soft clash : class-based individualisms in Manhattan and Queens / Adrie Kusserow -- Putting race in context : socioeconomic status predicts racial fluidity / Diana T. Sanchez and Julie A. Garcia -- The secret handshake : trust in cross-class encounters / Susan T. Fiske, Miguel Moya, Ann Marie Russell, and Courtney Bearns -- Index.